Cognitive foundations of leadership skills in early childhood: An empirical study - Chen, Rubin; Ong, Eng Tek; Pan, Lingle (Cognitive development, 2025)
This research identifies the possible development of leadership characteristics in young children and concepts related to the leadership characteristics. A quantitative research design was used, using surveys with 198 preschool teachers and 193 preschoolers' parents. The research reveals a significant potential for developing children's leadership characteristics through key parental modeling, suggesting engagement to ensure positive parental examples for children. Peer relations were identified as crucial in the development of leadership potential, emphasizing the social alternative aspect of development at an early age. The current study also considers many distinctive aspects of the context, including teacher-child interactions, enriched learning environments, communication, cultural contexts, and pedagogical relations, which, as a whole, led to understanding how and when new forms of leadership behaviors are developing for preschoolers. This study provides evidence and explanations for the emergence and development of leadership skills in young children, and how interdependent contexts can help them achieve social learning goals effectively, thereby enriching the academic literature with new knowledge. This study also has implications for educators and parents. It suggests that developing role models and making peer connections, and developing enriched learning environments have the potential to first, develop leadership skills, and second, develop some qualities associated with leadership within children. •Parental modeling strongly predicts preschoolers' leadership development.•Peer interactions significantly shape early leadership traits in group settings.•Enriched learning environments foster diverse leadership behaviors in children.•Communication skills are key to preschoolers' leadership emergence.•Cultural values and teacher-child bonds influence leadership expression in kids.